Tres prototipos de arquitectura efímera como experiencia cultural y turística en el departamento del Huila (2021)
Huila is one of the departments with the highest tourist and cultural activity in the country, despite this growing phenomenon, the department does not have enough spaces to enhance this important quality. In order to reduce the deficit of these spaces, the objective of this degree project is to develop three prototypes of ephemeral and itinerant pavilions in the municipalities of Neiva, Villavieja and San Agustín. Mainly aimed at young people and tourists as a target population, therefore, each prototype is made up of digital, modern and innovative spaces, which in turn can be adapted to the location where it is going to be implanted and the weather factor of each municipality. In this way, the strategies are reflected both in the exterior part of the project, due to its visual appeal and constructive factor, as well as in each spatial unit where there are digital artifacts that will focus on interacting with the user and thus promoting tourism. and culture for the natives as well as for the tourists who visit the department of Huila.